Relationship between productivity and efficiency with sustainable development goals: The case of the manufacturing industry in Pichincha, Ecuador; Relación entre productividad y eficiencia con los objetivos de desarrollo sostenible - Juan Ibujés-Villacís; Antonio Franco-Crespo (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
In 2015, at the United Nations forum, the 17 Sustainable Development Goals (SDGs) were approved to be met by 2030. This research aims to know what has been the behavior of productivity and efficiency of the manufacturing industry in the province of Pichincha, Ecuador, and the relationship with the achievement of some goals of the SDG 8, 9 and 12. The research methodology has a quantitative, non-experimental, and longitudinal approach. The information from the economic and financial reports of the manufacturing companies between 2010 and 2018 was processed. The values of efficiency were estimated using the data enveloping analysis technique. With the annual information, the evolution of productivity and efficiency was predicted until 2022. In the nine years, the results show that the productivity indicators and the number of companies that are related to goals 8.2 and 8.3 depend on the size of the companies and would maintain a constant trend until 2022. In addition, in the same period, it was shown that efficiency has had variations, and its trend is to remain constant until 2022, which shows that there will be no progress in meeting the targets 9.4, and 12.2 of the SDGs for this industrial sector.
Keywords: C14; D61; L25; L6; Q01; 330; data envelopment analysis; efficiency; forecast; manufacturing industry; productivity; sustainable development goals